Adding intermittent vibration to varied-intensity work intervals: No extra benefit - Bossi, A. H.; Mesquida, C.; Hopker, J.; Rønnestad, B. R. (International Journal of Sports Medicine, 2023)
Varied-intensity work intervals have been shown to induce higher fractions of maximal oxygen uptake during high-intensity interval training compared with constant-intensity work intervals. We assessed whether varied-intensity work intervals combined with intermittent vibration could further increase cyclists` fraction of maximal oxygen uptake to potentially optimise adaptive stimulus. Thirteen cyclists (V?O2max: 69.7±7.1 ml·kg-1·min-1) underwent a performance assessment and two high-intensity interval training sessions. Both comprised six 5-minute varied-intensity work intervals within which the work rate was alternated between 100% (3×30-second blocks, with or without vibration) and 77% of maximal aerobic power (always without vibration). Adding vibration to varied-intensity work intervals did not elicit a longer time above ninety percent of maximal oxygen uptake (415±221 versus 399±209 seconds, P=0.69). Heart rate- and perceptual-based training-load metrics were also not affected (all P=0.59). When considering individual work intervals, no between-condition differences were found (fraction of maximal oxygen uptake, P=0.34; total oxygen uptake, P=0.053; mean minute ventilation, P=0.079; mean heart rate, P=0.88; blood lactate concentration, P=0.53; ratings of perceived exertion, P=0.29). Adding intermittent vibration to varied-intensity work intervals does not increase the fraction of maximal oxygen uptake elicited. Whether intermittent exposure to vibration can enhance cyclists` adaptive stimulus triggered by high-intensity interval training remains to be determined.